Symptomatic Intracranial Atherosclerosis in an Australian Context: Common and Underdiagnosed in Multiple Ethnic Groups - Davor Pavlin‐Premrl; Michael Waters; Vincent Thijs; Peter J. Mitchell; Nawaf Yassi; Mark W. Parsons; Louise Weir; Lauren Pesavento; Julian Maingard; Geoffrey Cloud; Vimal Stanislaus; Mei Ngun; et al. (Stroke: Vascular and Interventional Neurology)
Background Intracranial atherosclerosis (ICAD) is a common cause of stroke globally. We calculated the proportion of patients with stroke with symptomatic intracranial atherosclerosis in an Australian multiethnic setting, as well as diagnostic rates by stroke physicians and radiologists. Methods This was a multicenter retrospective cohort study based in Melbourne, Australia. Demographic data (including self‐reported ethnicity) and data on vascular risk factors were collected. Symptomatic ICAD was independently identified by 2 blinded stroke neurologists using multiplanar reformats and maximum intensity projections of routinely acquired thin slice computed tomography angiography data, with disagreements resolved by a third blinded stroke neurologist. This diagnostic reference standard was compared to the proportion of patients with ICAD identified in the radiology report and stroke team clinical notes. Results Of 1328 patients included (mean age, 73 years; 43% female), the proportion of patients with centrally read symptomatic ICAD was 14%, of whom 39% were diagnosed by the stroke clinical team and 65% by the reporting radiologist. Patients of Asian ethnicity more commonly had symptomatic ICAD than patients of European ethnicity (21% versus 14%; odds ratio, 1.5 [95% CI, 1.0–2.23]). Conclusion Intracranial atherosclerosis is common and underdiagnosed in an Australian tertiary stroke care unit setting in patients from multiple ethnic backgrounds.